(untitled) (Research, Society and Development, 2020)
Campomanesia eugenioides, Campomanesia xanthocarpa (Berg) and Campomanesia xanthocarpa var. littoralis are native fruits plants distributed in Brazil, which are popularly recognized for their nutritional, economic and cultural values. Given the scarcity of the controlled scientific studies comparing native Campomanesia varieties, the objective of this study was to characterize the fruits of Campomanesia eugenioides, Campomanesia xanthocarpa and Campomanesia xanthocarpa var. littoralis, regarding chemical composition and nutritional value through the quantification of carbohydrates, lipids, moisture, ash, proteins and fibers; the minerals Ca, Mg, P, Cu, Zn, Mn, Fe, K, Na content; vitamin C and carotenoids content. These varieties showed distinct physicochemical characteristics with small differences mainly about ash content and caloric values. Nevertheless, C. xanthocarpa var. littoralis showed higher values for fiber content, total soluble solids, and total titratable acidity. C. eugenioides species highlighted in relation to the vitamin C and mineral contents, with an exception for C. xanthocarpa var. littoralis that showed higher iron content. C. xanthocarpa had the highest carotenoid content, confirming that these fruits have functional properties and high nutritional value. Finally, this study will provide important scientific data supporting the application of valuable fruits from three edible Campomanesia species for producing bioactive ingredients and natural preservatives for food products.